Tinjauan Manajemen Risiko Usahatani Jagung pada Lahan Miring di Desa Bonedaa Kecamatan Suwawa Selatan Kabupaten Bone Bolango - Mu'min Oki; Agustinus Moonti; Ramlan Mustafa (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Risk management is essential to anticipate potential risks for corn farmers in Bonedaa Village, Suwawa Selatan Sub-district, and Bone Bolango Regency. One is the risk faced on the sloping land conditions owned by farmers. This study aims to (1) identify the risks farmers face in Bonedaa Village and (2) examine the risk management practices implemented to mitigate risks in corn farming in sloped land in Bonedaa Village. The benefits of this research are that it is a source of information for farmers related to the application of risk management for corn farming carried out on sloping land conditions so that farmers can overcome the risk that will occur. The study was conducted among corn farmers in Bonedaa Village over to Mons from June to July 2024 and involved 34 farmer respondents. The study employed a survey method, utilizing a questionnaire to collect the data. This study applied descriptive analysis to determine the risk encountered by farmers and HIRARC analysis to identify risk management performed within the corn farming risk anticipation in the sloped land. The findings reveal that: (1) farmers in Bonedaa Village face various risks, including production risks caused by increased costs and crop failure. These risks significantly affect profits and losses, where higher production risks correspond to greater income risks, leading to potential losses for farmers. (2) Risk management in Bonedaa Village was analyzed using the HIRARC method, identifying seven key risks faced by farmers: increased labor costs for land clearing, crop failure due to water shortages during prolonged drought, crop damage from heavy rainfall, decreased yields due to pests and diseases, prolonged harvest time due to sloped terrain, increased labor costs during harvest, and high transportation costs due remote, difficult road access. The average risk score was categorized as “High” (10). Additionally, farmers have implemented control measures for some risks, such as increasing labor costs for land clearing and addressing drought and fast issues. However, several risks remain unmanaged due to a lack of knowledge of effective mitigation strategies.